Pengaruh Integritas Dan Kompensasi Terhadap Produktivitas Kerja Pegawai Toyota Auto 2000 Tanjung Api Api - Aniks, Mufadhal; Hadjri, Muhammad Ichsan; Siregar, Lina Dameria (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to analyze the influence of integrity and compensation on the work productivity of Toyota Auto 2000 Tanjung Api-Api employees. The population of this study were employees of Toyota Auto 2000 Tanjung Api-Api, and the sample for this study was 85 people. The data analyzed comes from answers to questionnaires distributed to respondents. The research results found that integrity and compensation partially or simultaneously influence the work productivity of Toyota Auto 2000 Tanjung Api-Api employees. Based on the results of this research, it is recommended that leaders be able to provide appropriate and fair compensation to employees, as well as provide support such as conducting work evaluations, planning and implementing skills development and paving the way for employees to improve their careers. Meanwhile, employees are expected to try to organize themselves, create high integrity in the work they do so that they can produce good work productivity